Does Video Dubbing Project Affect EFL Students' Self-Efficacy and Proficiency in English? - Nadrotin Mawaddah (Fakultas Bahasa dan Seni UNP, 2024)
Video Dubbing, or adding translated dialogues into a film or series, has been applied as a learning method in EFL speaking courses. Students can download videos from any platform and record their voice-overs in English. Previous research primarily studied the effect on students' skills. The impact on motivation, confidence, and self-efficacy is still worth exploring. Therefore, this research examined the effectiveness of the Video Dubbing Project on EFL students' self-efficacy and proficiency in speaking. This research design is Mixed-methods, which are pre-experiment and descriptive qualitative. The subjects were 38 students in grade 9 of junior high school in Situbondo, Indonesia. The result showed that it was significantly effective in improving self-efficacy and proficiency. However, based on the qualitative data, this project was simple for proficient students, but for those with low self-efficacy, the absence of a requirement to show their faces on camera empowered them to attempt this project. Upon completing their videos, they often express surprise and satisfaction by saying,